Transformation of Kyai Authority in Marriage: A Law-Abiding Society in Pekoren, Rembang, Pasuruan - M. Harir Muzakki; Euis Nurlaelawati; Ahmad Bunyan Wahib (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This article discusses the role and authority of kyai in marriage practices in Muslim communities, especially in Pekoren Rembang Village, Pasuruan. This research uses a socio-legal approach and focuses on the role of kyai in carrying out marriages that are not always registered at the Office of Religious Affairs (KUA). In the Pekoren community, kyai have authority in religious law and are often involved in the marriage contract procession, even though the KUA does not officially record it. This gives rise to unregistered marriages, where marriages are considered religiously valid but not recognized by the state. This research also reveals that the role of kyai in marriage has shifted due to increasing legal awareness in society, pragmatism, and reduced appreciation for Islamic boarding school graduates. This research concludes that the authority of kyai in marriage practices in Pekoren is decreasing along with socio-economic changes and increasing legal awareness in society. Now, people prefer marriages officially registered by the head of the KUA to obtain legal guarantees. The shifting role of kyai in marriage practices in Pekoren Village can serve as a guide for policymakers and religious leaders in ensuring that marriages are recognised under state law, in line with socio-economic changes and the legal awareness of the community.